Anatomical considerations in adult femoral neck fractures: How anatomy influences the treatment issues?. Issue 3 (March 2015) - Li, Mengnai; Cole, Peter A.
Abstract Femoral neck fractures in physiologically young adults are relatively uncommon. The reported incidence of avascular necrosis and nonunion rates remain relatively high despite the advancement in understanding and surgical management. Understanding the normal femoral neck anatomy and its relationship to presenting fracture pathology in young adults could help to lessen reported high complication rates to provide better clinical outcomes.